The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1074/jbc.m110.131003
|View full text |Cite
|
Sign up to set email alerts
|

Postendocytic Sorting of Constitutively Internalized Dopamine Transporter in Cell Lines and Dopaminergic Neurons

Abstract: The dopamine transporter (DAT) mediates reuptake of released dopamine and is the target for psychostimulants, such as cocaine and amphetamine. DAT undergoes marked constitutive endocytosis, but little is known about the fate and sorting of the endocytosed transporter. To study DAT sorting in cells lines, we fused the one-transmembrane segment protein Tac to DAT, thereby generating a transporter (TacDAT) with an extracellular antibody epitope suited for trafficking studies. TacDAT was functional and endocytosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 59 publications
(85 reference statements)
7
79
0
Order By: Relevance
“…Molecular Biology-The generation of plasmids encoding FLAG-tagged TacDAT (pcDNA3 TacDAT) and TacDAT C24 (pcDNA3 TacDAT C24) and mycPICK1 (pCMV mycPICK1) was described previously (43,44). The eGFP-tagged Rab constructs (pEGFP-C1 Rab7 and pEGFP-C1 Rab11) were a kind gift from Dr. Katherine W. Roche, National Institute of Neurological Disorders and Stroke, National Institutes of Health, Bethesda, MD (45).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular Biology-The generation of plasmids encoding FLAG-tagged TacDAT (pcDNA3 TacDAT) and TacDAT C24 (pcDNA3 TacDAT C24) and mycPICK1 (pCMV mycPICK1) was described previously (43,44). The eGFP-tagged Rab constructs (pEGFP-C1 Rab7 and pEGFP-C1 Rab11) were a kind gift from Dr. Katherine W. Roche, National Institute of Neurological Disorders and Stroke, National Institutes of Health, Bethesda, MD (45).…”
Section: Methodsmentioning
confidence: 99%
“…1b, upper panel). However, when we fused the entire DAT sequence to Tac and coexpressed the resulting construct (TacDAT) (43) (Fig. 1a) in the Flp-In T-REx 293 eYFP-PICK1 cells, we did not see any signs of eYFP-PICK1 clustering (Fig.…”
Section: Pick1 Co-clusters Only With Subset Of Its Interaction Partners-mentioning
confidence: 99%
“…Accordingly, it was proposed that the intracellular transporters represented a recruitable transporter pool permitting rapid mobilization of transporter to the surface during periods of high signaling activity. However, for DAT, it has recently been suggested that a substantial fraction of the constitutively internalized DAT is sorted to a lysosomal/degradative pathway with probably only a rather small fraction sorted to Rab4-positive "short-loop" recycling pathways (Eriksen et al, 2010a).…”
Section: Endocytic Traffickingmentioning
confidence: 99%
“…JHC 1-064 was previously shown to preferentially label surface expressed dopamine transporter [10]. To correct for spectral bleed-through, background measurements were taken in the donor channel (DD; excitation and emission wavelengths for YFP are 514 and 527 nm respectively) and in the FRET channel (DA; excitation wavelength for YFP is 514 where emission wavelength for rhodamine is 585 nm) separately and all values were corrected with respect to background.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%